Effect of Cuscuta epithymum Acquainted with Risperidone on the Improvement of Clinical Symptoms and Cognitive Impairment in Patients with Schizophrenia: A Triple-Blind Randomized Placebo-Controlled Trial: - Parvizi, Maedeh; Fadai, Farbod; Khodaei-Ardakani, Moahammad Reza; Amin, Gholamreza; Abdi, Leila; Noroozi, Mehdi; Ansari, Iman (Galen Medical Journal, 2019)
Background: Cuscuta epithymum (CE) is an established medicinal herb utilized for treating psychosis in Persian medicine. The aim of this study was to investigate the effect of CE combined with risperidone on the clinical symptoms and the cognitive impairment in patients diagnosed with schizophrenia. Materials and Methods: In this triple-blind randomized placebo-controlled trial, the intervention group received a dose of 500 mg of CE in the form of a capsule to be taken twice a day accompanied by an appropriate dose of risperidone. The control group was presented with a placebo identical to that of the CE capsule plus the allocated dose of risperidone. The PANSS and SCoRS questionnaires were used to assess the status of subjects prior to the initiation of the intervention as well as being put to use at the end of the second, fourth, and eighth week post-intervention. Registering and recording intel concerning positive and negative symptoms felt by participants (PANNS), and a test to assess the cognitive impairment of the individuals. Results: After eight weeks of treatment, all negative and positive symptoms besides hostility and somatic concern exhibited a significant improvement in the CE group (P <0.05). In contrast, the CE placebo group displayed no substantial improvement in the cases of the positive, negative and general symptoms (P>0.05) regarding cognitive impairment, after eight weeks of treatment, all symptoms were greatly improved in the CE group (P<0.05), while the effect of the placeboÂ  on the patients cognitive impairment remained mostly stationary (P>0.05). Consequently, after eight weeks after the intervention, we can determine that the CE treatment has been noticeably more effective at improving positive, negative and cognitive symptoms of patients with schizophrenia. Conclusion: The results of this study demonstrated that CE, possessing possible antioxidant and neuroprotective properties, safely improved the positive and negative symptoms, and cognitive impairment of patients with schizophrenia.[GMJ.2019;8:e1334]Â 